The theory of relativity and its influence on scientific thought - Eddington, Arthur Stanley, Sir, 1882-1944 (Salt Lake City, UT : Project Gutenberg, 2023)
"The theory of relativity and its influence on scientific thought" by Eddington is a scientific publication delivered as the Romanes Lecture in 1922. The book discusses the revolutionary implications of Einstein's theories of relativity on our understanding of space and time, marking a significant shift in scientific thought from a geocentric to a more abstract and relativistic perspective. In this lecture, Eddington explains how Einstein's theories challenge long-held notions of fixed frames of reference, asserting that the measurements of space and time are relative to the observer$1 (Bs motion. He elaborates on concepts such as the FitzGerald contraction and how they arise from the need to view physical phenomena without the distortions imposed by our earthly point of view. By illustrating the relativity of physical laws and the geometry of the universe, Eddington emphasizes the profound impact of Einstein's work on fields like mechanics and gravitation, arguing that a new understanding of the four dimensions of space-time reshapes not only physics but also our broader comprehension of existence in the cosmos. (This is an automatically generated summary.)s
Release date is 2023-03-12
Laura Natal Rodrigues (Images generously made available by Hathi Trust Digital Library.)
Keywords: Relativity (Physics); Science -- Philosophy